Excess Body Mass Index Loss at 3 Months: A Predictive Factor of Long-Term Result after Sleeve Gastrectomy. (29th January 2017) - Philouze, Guillaume; Voitellier, Eglantine; Lacaze, Laurence; Huet, Emmanuel; Gancel, Antoine; Prévost, Gaëtan; Bubenheim, Michael; Scotté, Michel
Abstract : Introduction. Laparoscopic Sleeve Gastrectomy (SG) is considered as successful if the percentage of Excess Body Mass Index Loss (% EBMIL) remains constant over 50% with long-term follow-up. The aim of this study was to evaluate whether early % EBMIL was predictive of success after SG. Methods. This retrospective study included patients who had SG with two years of follow-up. Patients had follow-up appointments at 3 (M3), 6, 12, and 24 months (M24). Data as weight and Body Mass Index (BMI) were collected systematically. We estimated the % EBMIL necessary to establish a correlation between M3 and M24 compared to % EBMIL speeds and calculated a limit value of % EBMIL predictive of success. Results. Data at operative time, M3, and M24 were available for 128 patients. Pearson test showed a correlation between % EBMIL at M3 and that at M24 (r = 0.74 ; p < 0.0001 ). % EBMIL speed between surgery and M3 (p = 0.0011 ) was significant but not between M3 and M24. A linear regression analysis proved that % EBMIL over 20.1% at M3 (p < 0.0001 ) predicted a final % EBMIL over 50%. Conclusions. % EBMIL at M3 after SG is correlated with % EBMIL in the long term. % EBMIL speed was significant in the first 3 months. % EBMIL over 20.1% at M3 leads to the success of SG.